Solutal and thermal buoyancy effects in self-powered phosphatase micropumps. Issue 15 (27th March 2017) - Valdez, Lyanne; Shum, Henry; Ortiz-Rivera, Isamar; Balazs, Anna C.; Sen, Ayusman
Abstract : Surface-immobilized phosphatases exposed to reactants generate fluid flow with velocities depending on the density difference between reactants and products. Abstract : Immobilized enzymes generate net fluid flow when exposed to specific reagents in solution. Thus, they function as self-powered platforms that combine sensing and on-demand fluid pumping. To uncover the mechanism of pumping, we examine the effects of solutal and thermal buoyancy on the behavior of phosphatase-based micropumps, using a series of reactants with known thermodynamic and kinetic parameters. By combining modeling and experiments, we perform the first quantitative comparison of thermal and solutal effects in an enzyme micropump system. Despite the significant exothermicity of the catalyzed reactions, we find that thermal effects play a minimal role in the observed fluid flow. Instead, fluid transport in phosphatase micropumps is governed by the density difference between the reactants and the products of the reaction. This surprising conclusion suggests new design principles for catalytic pumps.